To cross the own skin - Manuela Avilés Martos (Arteterapia)
We present the work developed in last years in the Workshops of Creativity of the Major Classroom, Granada University, which participants have been fundamentally women between 50 and 70 years old. The perspective of work uses an artistic practice related with art education and feminist process. In the workshops the approximation has been looked to the commonness of these women, from a learning interested for checking critically the cultural production in art, with the intention of demythologizing the plastic creation, the construction of feminine identity and of waking up in the participants the attitude and the interest to explore and to expand his own identity.